2006
DOI: 10.1186/1471-2407-6-195
|View full text |Cite
|
Sign up to set email alerts
|

The role of sialomucin CD164 (MGC-24v or endolyn) in prostate cancer metastasis

Abstract: Background: The chemokine stromal derived factor-1 (SDF-1 or CXCL12) and its receptor CXCR4 have been demonstrated to be crucial for the homing of stem cells and prostate cancers to the marrow. While screening prostate cancers for CXCL12-responsive adhesion molecules, we identified CD164 (MGC-24) as a potential regulator of homing. CD164 is known to function as a receptor that regulates stem cell localization to the bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 41 publications
1
75
0
Order By: Relevance
“…PCa-induced osteolysis may be due to both inhibitory effects on osteoblasts and stimulatory effects on osteoclasts by enhanced OPN secretion by osteoblasts. 99 We have also reported that the CXCL12/CXCR4 chemokine axis plays a significant role in the bone metastasis of PCa, [19][20][21][22][23] by activating avb3 integrins 23 and CD164.…”
Section: Molecular Parasites Of the Nichementioning
confidence: 99%
See 1 more Smart Citation
“…PCa-induced osteolysis may be due to both inhibitory effects on osteoblasts and stimulatory effects on osteoclasts by enhanced OPN secretion by osteoblasts. 99 We have also reported that the CXCL12/CXCR4 chemokine axis plays a significant role in the bone metastasis of PCa, [19][20][21][22][23] by activating avb3 integrins 23 and CD164.…”
Section: Molecular Parasites Of the Nichementioning
confidence: 99%
“…17,18 On the basis of our studies relating to the HSCs homing, we have recently reported the significant role of the chemokine CXC chemokine ligand 12 (CXCL12 or SDF-1)/its major receptor CXC chemokine receptor 4 (CXCR4) axis on the bone metastasis of Pca. [19][20][21][22][23] Although the mechanisms of bone metastasis are still unclear, the CXCL12/CXCR4 chemokine axis is likely to play a significant role in regulating the bone metastasis of solid neoplasms. Thus, several lines of evidence demonstrate that bone marrow stromal cells are also able to promote the growth, survival and drug resistance of hematogenous neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…In human cancers, CD164 was reported played roles in many different cancers. For instance, CD164 has been reported for the maintenance and progression of human tumors, such as human glioma,13 lung cancer,14 ovarian cancer,15 and prostate cancer 16. Besides, some microRNAs such as miR‐124 and miR‐219 were found that could suppress the proliferation, migration, and invasion of tumor cells by targeting CD164 17, 18.…”
Section: Introductionmentioning
confidence: 99%
“…CXCL12 is known for is strong chemoattraction for lymphocytes during embryogenesis where it directs migration of hematopoietic cells from the foetal liver to the bone marrow for the formation of large blood vessels [34,35]. In adults, SDF-1/CXCL12 maintains a similar role in angiogenesis and this is observed in prostate cancer cell metastasis to the bone where CXCL12 initiates its signaling through the CXCR4 receptor to activate expression of alpha-vb3-integrins (cell surface receptors that play a role in adhesion, migration, invasion, growth and angiogenesis) [36] and CD164 (an adhesive factor involved in haematopoiesis) [37]. This causes down regulation in the expression of the glycolytic enzyme phosphoglycerate kinase 1 (PGK1) and angiostatin in parallel to secretion of VEGF and tissue inhibitor of metalloproteases 2 (TIMP2) via the PI3K/Akt pathway [38].…”
Section: The Primary Tumour Microenvironmentmentioning
confidence: 99%